Form-stable benzoxazine-urethane alloys for thermally reversible light scattering materials - T. Parnklang (eXPRESS Polymer Letters, 2019)
Thermally reversible light scattering (TRLS) materials based solely on benzoxazine-urethane (BA-a/PU) alloys were successfully fabricated and demonstrated in this work. The alloys displayed the opaque state below 40 °C. The alloys were transformed to the transparent state upon exposing to the transition temperature of 60–130 °C, depending on the molecular weights and mass concentrations of urethane prepolymers in the BA-a/PU alloys. The optical state transitions were reversible with small hystereses. BA-a/PU alloys exhibited a good optical contrast with 0%T at the light scattering state and almost 100%T at the transparent state. The alloys were glassy and form-stable up to 250 °C, due to the synergistic behavior in the glass transition temperatures. The reaction-induced phase separation effectuated by the incorporation of urethane prepolymer into thermosetting polybenzoxazine, the sizes and local concentrations of the phase-separated urethane microdomains in the supporting polybenzoxazine matrix, and the reversible dissolution and demixing of urethane microdomains and polybenzoxazine phase played crucial roles on TRLS properties of the developed benzoxazine-urethane alloys.